Fault location estimation method by considering measurement error for distribution networks - Mokhlis, Hazlie (Wiley, 2014)
This paper proposes a fault location estimation method for distribution networks considering errors from measurement devices. The method determines the fault location based on the voltage sag and current magnitudes. The fault location is based on faulted section and fault distance measured from one end of the bus. Faulted section is determines by matching the measured voltage and current with a pre-developed data. For multiple faulted sections, ranking analysis is employed to rank the most likely faulted section. Fault distance is calculated from one end of the identified faulted section. By determining the faulted sections, a fault in homogenous and non-homogenous networks can be located. The method has been tested using an actual Malaysian 11 kV distribution network. Different values of measurement errors have been applied, which includes positive and negative values. The test results showed the effectiveness of the method under various uncertainty of error from measurement devices. The proposed method can serve as an alternative technique for estimating fault location in distribution networks.